1991
DOI: 10.1136/jech.45.3.184
|View full text |Cite
|
Sign up to set email alerts
|

Chronic leg ulcers: an underestimated problem in primary health care among elderly patients.

Abstract: Study objective-The aim was to establish leg ulcer point prevalence, basal patient characteristics, and level of caretaking.Design-The study was a postal cross sectional survey. The Participants-827 individual patients were found with active leg ulcers, 526 women and 301 men.Measurements and main results-Age adjusted sex ratio of ulcer patients was 1:1-4 (M:F). The median age was 78 years for women and 76 for men; 700 patients (85%) were older than 64 years. The point prevalence for active leg ulcers was 3-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
2
5

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(111 citation statements)
references
References 3 publications
4
100
2
5
Order By: Relevance
“…These results were found to be below the average determined by Nelzen et al 9 (Switzerland), in whose sample 85% were over the age of 64 years with a mean age of 76 years for women and 78 for men. By contrast, the results were similar to Scott et al 10 These difference are justified by different techniques used to collect data, in addition to socioeconomic, cultural and geographic differences characteristic of each sample.…”
Section: Discussioncontrasting
confidence: 42%
“…These results were found to be below the average determined by Nelzen et al 9 (Switzerland), in whose sample 85% were over the age of 64 years with a mean age of 76 years for women and 78 for men. By contrast, the results were similar to Scott et al 10 These difference are justified by different techniques used to collect data, in addition to socioeconomic, cultural and geographic differences characteristic of each sample.…”
Section: Discussioncontrasting
confidence: 42%
“…Chronic wounds were found to predominantly affect elderly patients. Studies in Europe have shown that the prevalence of chronic wounds increases with advancing age from 1.48/1,000 to 36/1,000 population in those over 65 years of age [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Severe manifestations and ulceration occur in 4% to 6% and 7% to 23%, respectively [7,8]. The prevalence of venous ulceration is at least 300 per 100000 and approximately 25% are due to DVT [9,10]. In the United States, skin changes and ulceration are present in 6 to 7 million and 400,000 to 500,000 people, respectively [11].…”
Section: Introductionmentioning
confidence: 99%